Arthroschista Hilaralis: The Biology and Emerging Threat to Kadam (Anthocephalus Cadamba) Sapling in Sylhet, Bangladesh (Bangladesh Journal of Zoology, 2021)
In Sylhet, nursery owner facing a lepidopteran pest problem namely Arthroschista hilaralis on kadam saplings. Therefore, our research was articulated to find out the insect biology and damage severity of A. hilaralis on kadam saplings. Larvae of A. hilaralis folding the kadam leaves and make it entirely skeletonize. Whitish round shaped eggs were laid in cluster at both upper and lower surface of kadam leaves. Eggs were hatched after 6.4±0.2 days and the larval stage remained 12.8±0.3 days which was the main dangerous stage for kadam saplings. The full-grown caterpillars were around 21.5 mm to 25.0 mm in length. Pupal stage required around 6.4±0.6 days to became an adult moth. These insects damaged tender branches and young leaves of kadam saplings in June to October, 2018.Bangladesh J. Zool. 49(1): 83-90, 2021